1981
DOI: 10.1128/iai.31.1.21-27.1981
|View full text |Cite
|
Sign up to set email alerts
|

Eikenella corrodens adherence to human buccal epithelial cells

Abstract: The mechanism of Eikenella corrodens adherence to human buccal epithelial cells in vitro was studied. Initial experiments to determine the optimal conditions for adherence of E. corrodens to buccal epithelial cells showed that adherence was dependent on time, temperature, bacterial concentration, and pH. Different strains of E. corrodens varied in their ability to adhere, and strain 1073 showed the greatest ability in adherence. Strain 1073 was selected for studies of adherence mechanisms. Trypsin treatment or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…First, the adherent ability of P. gingivalis to cultured human fibroblasts such as Gin I cells and human periodontai ligament fibroblasts and epithelial cells (Ca9-22) was examined. Many investi- gators have reported bacterial attachment to buccal cells collected by scraping the oral mucosal surface (23,26,34,45). In this experiment, we used cultured cells originating from human buccal regions as the target cells in order to prevent the experimental error caused by the variation in volunteer cells.…”
Section: Discussionmentioning
confidence: 99%
“…First, the adherent ability of P. gingivalis to cultured human fibroblasts such as Gin I cells and human periodontai ligament fibroblasts and epithelial cells (Ca9-22) was examined. Many investi- gators have reported bacterial attachment to buccal cells collected by scraping the oral mucosal surface (23,26,34,45). In this experiment, we used cultured cells originating from human buccal regions as the target cells in order to prevent the experimental error caused by the variation in volunteer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivity of antibodies to E. corrodens 1073 and E. corrodens 1 080 tination activity than E. corrodens 1073 cells did (13,15). In addition, coaggregation activity of E. corrodens 1080 with A. vis casus or S. sanguis was weaker than that of E. corrodens 1073 (data not shown).…”
Section: Characterization Ol Monoclonal Antibodiesmentioning
confidence: 89%
“…Monoinfection of germfree, or gnotobiotic rats with E. corrodens 1073 has been re-ported to cause periodontal disease with sever alveolar bone loss (10)(11)(12). Previously, we found that E. corrodens I 073 had a cell-associated lectinlike substance (EeLS) and it functioned in the adherence of this oral bacterium to various cell surface (13)(14)(15). We also found that EeLS mediated N-acetyl-D-galactosamine (GalNAc)-inhibitable coaggregation of E. corrodens with certain strains of Streptococcus sanguis and Actinomyces l'iscosus in vitro ( 16) which were prominent in the earliest stages of plaque formation (8,17).…”
mentioning
confidence: 99%
“…Corynebacterium parvum has also been shown to bind to phagocytes by a mannose-specific lectin binding site in the cell wall of the bacterium [20]. Other microorganisms that rely on lectin type adhesion are Klebsiella pneumonia, various species of Salmonella, Shigella and Proteus [8, 21,22], Eikenella corrodens, Aeromonos hydrophilia and Fusobacterium nucleatum [23][24][25].…”
Section: Type 1 Interactions --Bacterial Lectins As Adhesinsmentioning
confidence: 99%